Downregulation of PTEN Promotes Autophagy via Concurrent Reduction in Apoptosis in Cardiac Hypertrophy in PPAR α−/− Mice - Kumari, Ritu; Ray, Aleepta Guha; Mukherjee, Dibyanti; Chander, Vivek; Kar, Dipak; Kumar, Uppulapu Shravan; Bharadwaj P.V.P., Deepak; Banerjee, Sanjay K.; Konar, Aditya; Bandyopadhyay, Arun (Frontiers in Cardiovascular Medicine, 2022)
Cardiac hypertrophy is characterized by an increase in the size of the cardiomyocytes which is initially triggered as an adaptive response but ultimately becomes maladaptive with chronic exposure to different hypertrophic stimuli. Prolonged cardiac hypertrophy is often associated with mitochondrial dysfunctions and cardiomyocyte cell death. Peroxisome proliferator activated receptor alpha (PPAR α), which is critical for mitochondrial biogenesis and fatty acid oxidation, is down regulated in hypertrophied cardiomyocytes. Yet, the role of PPAR α in cardiomyocyte death is largely unknown. To assess the role of PPAR α in chronic hypertrophy, isoproterenol, a β-adrenergic receptor agonist was administered in PPAR α knock out (PPAR α-/-) mice for 2 weeks and hypertrophy associated changes in cardiac tissues were observed. Echocardiographic analysis ensured the development of cardiac hypertrophy and compromised hemodynamics in PPAR α-/- mice .Proteomic analysis using high resolution mass spectrometer identified about 1200 proteins enriched in heart tissue. Proteins were classified according to biological pathway and molecular functions. We observed an unexpected down regulation of apoptotic markers, Annexin V and p53 in hypertrophied heart tissue. Further validation revealed a significant down regulation of apoptosis regulator, PTEN, along with other apoptosis markers like p53, Caspase 9 and c-PARP. The autophagy markers Atg3, Atg5, Atg7, p62, Beclin1 and LC3 A/B were up regulated in PPAR α-/- mice indicating an increase in autophagy. Similar observations were made in a high cholesterol diet fed PPAR α-/-mice. The results were further validated in vitro using NRVMs and H9C2 cell line by blocking PPAR α that resulted in enhanced autophagosome formation upon hypertrophic stimulation. The results demonstrate that in the absence of PPAR α apoptotic pathway is inhibited while autophagy is enhanced. The data suggest that PPAR α signalling might act as a molecular switch between apoptosis and autophagy thereby playing a critical role in adaptive process in cardiac hypertrophy.